Las etnías y lenguas aborígenes en Salta: Situación actual y perspectivas de evolución - Fernández Lávaque, Ana María (1997)
The objective of this work is to make a synthesis of the territorial and numerical distribution of the different aboriginal ethnic groups that inhabit the province of Salta (northwestern Argentina) and of the languages ​​used by them. Beforehand, however, some brief considerations that frame the data that we wish to present are necessary. It is well known that the second half of the last century represents the triumph, basically through the so-called Generation of 1980, of Sarmiento's ideas about considering the national language, that is, Spanish, as one of the characteristic elements of the country unit.